Biomedical Sensors and Measurement - Wang, Ping. (Advanced Topics in Science and Technology in China,, 2011)
"Biomedical Sensors and Measurement" is an interdisciplinary book combining electronics with biology and medicine. It gives an overview of the concept and principle of biomedical sensors and measurement. First, the basic theory and technology are explained, followed by details of the physical sensors, chemical sensors, biosensors and their typical applications in biomedicine. Furthermore, the interface technology of the sensors and the typical measurement systems is presented. The large amount of vivid and specific figures and formulas will help to deepen the understanding of the fundamental and new applications involving biomedical sensors and measurement technology. The book is intended for biomedical engineers, medical physicists and other researchers and professionals in biomedicine-related specialties, especially interdisciplinary studies. Prof. Ping Wang and Dr. Qingjun Liu both work at the Biosensor National Special Laboratory, Key Laboratory for Biomedical Engineering of Education Ministry, Department of Biomedical Engineering, Zhejiang University, China.